2003
DOI: 10.1002/ajh.10345
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin concentrations in peripheral blood correlated with platelet numbers in two patients with thrombocytopenia by chronic graft‐versus‐host disease

Abstract: Thrombocytopenia is well known to be one of the clinical manifestations of chronic graft-versus-host disease (cGVHD). However, there exist cases in which the cause of thrombocytopenia has been unexplained. Recently, thrombopoietin (TPO) from bone marrow (BM) stromal cells and transforming growth factor (TGF)-␤ from platelets and megakaryocytes have been identified as strong positive and negative regulators of megakaryopoiesis in vivo. We hypothesized that the decreased TPO production from BM could be one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Circulating TGF-beta levels ranging from 5ng/ml to >20ng/ml have been described in both hematologic malignancies and solid tumor patients [ 19 23 ]. These levels are higher than seen in healthy volunteers and correspond with impaired cellular immunity [ 16 19 , 24 26 ]. Levels below 1ng/ml have been described in the peripheral blood and bone marrow of healthy volunteers [ 24 ] while acute myeloid leukemia and myelodysplastic syndrome patients have levels ranging from 6 to 42ng/ml [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating TGF-beta levels ranging from 5ng/ml to >20ng/ml have been described in both hematologic malignancies and solid tumor patients [ 19 23 ]. These levels are higher than seen in healthy volunteers and correspond with impaired cellular immunity [ 16 19 , 24 26 ]. Levels below 1ng/ml have been described in the peripheral blood and bone marrow of healthy volunteers [ 24 ] while acute myeloid leukemia and myelodysplastic syndrome patients have levels ranging from 6 to 42ng/ml [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…These levels are higher than seen in healthy volunteers and correspond with impaired cellular immunity [ 16 19 , 24 26 ]. Levels below 1ng/ml have been described in the peripheral blood and bone marrow of healthy volunteers [ 24 ] while acute myeloid leukemia and myelodysplastic syndrome patients have levels ranging from 6 to 42ng/ml [ 21 ]. In a study of 45 colorectal cancer patients, Narai et al reported circulating total TGF-beta levels greater than 15ng/ml in patients with metastatic disease [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thrombocytopenia at the time of chronic GvHD diagnosis has been associated with a poor prognosis (Sullivan et al , 1988a; Anasetti et al , 1989; Akpek et al , 2001a). Peripheral blood thrombopoietin concentrations may be decreased secondary to BM stromal cell damage (Hirayama et al , 2003). Eosinophilia may be seen and may be an indicator of chronic GvHD activity.…”
Section: Haematopoietic Systemmentioning
confidence: 99%
“…Thrombocytopenia because of low thrombopoietin (TPO) level is generally thought to be relatively rare; however, it has not been thoroughly investigated in the cGVHD setting. Hirayama et al 83 described two cGVHD patients with low platelet counts and strong correlations of platelet and megakaryocyte numbers with TPO concentrations in peripheral blood. They concluded that low TPO production may be responsible for thrombocytopenia in some cGVHD patients.…”
Section: Immune-mediated Thrombocytopeniamentioning
confidence: 99%